(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Postoperative pain responsible for neurohumoral changes which may cause various organ dysfunctions, prolong hospitalization and convalescence. Epidural analgesia confers excellent pain relief and complete dynamic analgesia leading to a substantial reduction in the surgical stress response. Objectives: The aim of the study was to compare the postoperative analgesic effect of dexmedetomidine and fentanyl as an adjuvant to epidural bupivacaine in adult patients undergoing hepatobiliary pancreatic surgery.Material and method: Eighty(80) patients were selected in the pre anaesthetic checkup room who were going to be operated for hepatobiliary pancreatic disorders. Each patient in group D(Dexmedetomidine group): Dexmedetomidine 2ml (100 µgm) was mixed with 48ml bupivacaine 0.125% in a syringe 50ml and infused epidurally @ 4ml/hr. for the postoperative 48 hours. Group F (fentanyl group): Fentanyl 2ml (100 µgm) was mixed with 48 ml bupivacaine 0.125% in a syringe 50 ml and infused epidurally @ 4ml/hr. for the postoperative 48 hours. Results: The quality of analgesia was almost similar with dexmedetomidine and fentanyl group but perioperative haemodynamic stability was more in dexmedetomidine group than fentanyl group (p=<0.05). The incidence of post-operative nausea and vomiting, pruritus, urinary retention and respiratory depression significantly lower with dexmedetomidine compared to fentanyl group (p=<0.05). Conclusion: Dexmedetomidine is an ideal adjuvant to epidural bupivacaine for postoperative analgesia compared to fentanyl in patients undergoing hepatobiliary pancreatic surgery. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 143-149